Kesepian dan Kecenderungan Nomophobia pada Mahasiswa - Andreas Corsini Widya Nugraha; Rijal Abdillah; Riyanti Oktavianingsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
The inability of individuals to manage themselves in using smartphones can have a negative impact, one of which is smartphone dependence. Nomophobia is the fear and anxiety of not being able to use a cell phone or smartphone or its features that are often experienced by young people. Individuals who have a tendency to nomophobia feel discomfort, anxiety, nervousness, or feel sad when they lose contact with their smartphone. Excessive smartphone use can lead to loneliness, as well as a source of loneliness itself. This study aims to determine the relationship between loneliness and the tendency of nomophobia in students at Bhayangkara University, Greater Jakarta. The researcher uses a quantitative method with a correlational approach, namely the Pearson correlation technique, and uses 266 student subjects. The results showed that there was a positive relationship between loneliness and the tendency of nomophobia with the value of the correlation coefficient (0.344), which means that the higher the loneliness, the higher the tendency for nomophobia. Keywords : Loneliness, Nomophobia